IoT-sustainability protection: water level monitoring with micro leak detection and automatic water restoration - Zainuddin, Ahmad Anwar; Bharudin, Mohamad Syafiq Asyraf; Kamarudin, Saidatul Izyanie; Amir Hussin, Amir 'Aatieff; Subramaniam, Krishnan; Mohd Tamrin, Mohd Izzuddin; Handayani, Dini Oktarina Dwi; Nik Mohd Kamal, Nik Nor Muhammad Saifudin (IEEE, 2024)
Efficient water resource management stands as a linchpin for sustainable development initiatives worldwide. To this end, this work endeavours to pioneer a comprehensive water level monitoring system with a focus on leak detection and automatic water restoration. Tailored with specialized sensors with cutting-edge automation technology to monitor water levels against predefined thresholds, promptly triggering restoration processes when necessary and identifying leaks in real-time. Central idea of the design is the incorporation of a dedicated rain sensor module, bolstering the micro leak detection capabilities while an ultrasonic sensor ensures precise measurement of water levels in tanks. In the event of a detected leak, rain sensor promptly initiates a signal, process by the main board which also known as the “brain” of the system and triggers an automatic cessation of water input to prevent wastage. Moreover, the system ensures seamless data logging by uploading pertinent information to a dedicated IoT cloud database, facilitating comprehensive monitoring and analysis. This innovative solution underscores not only its viability but also its practical efficacy, showcasing its potential to optimize water utilization and conservation efforts. Specifically, it excels in detecting micro droplets indicative of leaks in the tank. This work aims to spearhead the development of an advanced water level monitoring system, leveraging state-of-the-art of Arduino hardware and a diverse array of sensors, including ultrasonic and rain sensors as well as presenting a holistic framework poised to revolutionize water management practices.